The Qur’ānic Green Campus Model in Islamic Higher Education Indonesia - Fatah, Abdul; Khoiril Waro, Mochamad Tholib (Studia Ecologiae et Bioethicae, 2025)
This paper aims to explore the concept of Qur’ānic ecology and its relevance to the green campus concept in Islamic Higher Education Indonesia. This research is a qualitative with object study green campus practices at Universitas Islam Negeri (UIN) State Islamic University Walisongo, Semarang, and Universitas Islam Negeri (UIN) State Islamic University Raden Intan Lampung. The selection of these two universities is based on the release from UI GreenMetric which identify them as part of the top institutions in terms of green campus management. The paper argues the integration of Qur’ānic teachings on ecology and the green campus concept would be a new model of approach in protecting the environment as well as promoting a sustainable campus in Islamic higher education institutions. The Qur’ānic Green Campus is an innovative approach that integrates the Qur’ānic values on the environment with UI GreenMetric formulation. The results of this research aim to demonstrate that Qur’ānic teachings are not limited to discussions of eschatological matters